Incidence and prevalence of injuries in some sports - review - Gurau, T. V.; Musat, C. L.; Voinescu, D. C.; Anghel, L.; Gurau, G.; Postelnicu, M. G.; Stefanescu, C. A.; Onu, I.; Corciova, C.; Iordan, D. A. (Balneo and PRM Research Journal, 2023)
Injuries are an inherent risk associated with sports participation, impacting the health and performance of athletes across various disciplines. This review aims to provide a comprehensive analysis of the incidence and prevalence of injuries in selected sports, shedding light on the magnitude and patterns of injuries observed within each sport. To conduct this review, an extensive search was performed across electronic databases and relevant sports medicine literature. The findings reveal significant variability in injury rates and patterns among different sports. Sports such as football, handball, and volleyball, exhibit higher overall injury rates, with musculoskeletal injuries being most prevalent. Conversely, sports such as running, and cycling tend to demonstrate lower injury rates, with a focus on overuse injuries. Common injury types observed across sports include sprains, strains, fractures, contusions, and concussions, while body regions such as the lower extremities, head and neck, and upper limbs are frequently affected. Various factors contribute to the occurrence of injuries in sports, including player age, gender, skill level, training intensity, equipment usage, playing surface, and rule modifications. Contact and collision sports carry a higher risk of traumatic injuries compared to non-contact and individual sports. Understanding the incidence and prevalence of injuries in different sports is crucial for the development and implementation of injury prevention strategies. This review highlights the need for tailored approaches that address sport-specific risk factors, focusing on athlete education, proper training techniques, equipment modifications, rule changes, and enhanced medical support.